Analisis Partisipasi Masyarakat Dalam Program Konservasi Aliran Sungai Brang Biji Kabupaten Sumbawa Terhadap Kelestarian Lingkungan - Junaidi, Junaidi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Rivers are an important element in the hydrological cycle and have a crucial role in providing clean water, supporting plant and animal life, and meeting human needs in various sectors. This study aims to analyze the participation of the river flow community on the environmental sustainability of the Brang Biji River, Sumbawa Regency. This study uses a mixed research method that combines quantitative and qualitative approaches with data collection techniques through interviews with informants, direct field observations and distribution of questionnaires to respondents, namely the people in the Brang Biji river and other secondary data collection in the form of written data from various libraries and photographs. documentation during research. The results showed that the value of community participation in efforts to preserve the Brang Biji River was relatively low at 46.825%, which means that it was not yet included in the participation level of 62.50% - 81.24% which was declared